The multi-governance of water : four case studies - Finger, Matthias; Tamiotti, Ludivine, 1973-; Allouche, Jeremy (Albany : State University of New York Press, 2006)
As the governance of transboundary rivers becomes a subject of growing importance due to the increasing pressure on freshwater resources, this timely collection examines water scarcity and efforts to better manage rivers and river basins. Most specialists agree that states face many institutional inadequacies when dealing with shared resources and that new governance mechanisms are needed to improve water management. Using case studies of the Aral Sea basin and the Danube, Euphrates, and Mekong river basins, the contributors develop a new approach to water governance: the concept of multi-governance, an effort to collectively solve public problems by involving a series of relevant actors from the local to the global level, such as institutions, states, civil society, and business. Book jacket.
Introduction : conceptual elements / Matthias Finger, Ludivine Tamiotti & Jeremy Allouche -- The Mekong River Basin : comprehensive water governance / Nantana Gajaseni, Oliver William Heal and Gareth Edwards-Jones -- The Danube River Basin / Stephen McCaffrey -- The Euphrates River watershed : integration, coordination, or separation? / Arnon Medzini and Aaron T. Wolf -- The Aral Sea : legal and institutional aspects of governance / Laurence Boisson de Chazournes -- Conclusion : globalization, multi-governance, and transboundary river basin management / Matthias Finger, Ludivine Tamiotti & Jeremy Allouche.
Includes bibliographical references and index.
Print version record.
English.
Keywords: Water-supply -- Economic aspects -- Case studies; Water-supply -- Management -- International cooperation -- Case studies; Water resources development -- International cooperation -- Case studies; Watershed management -- International cooperation -- Case studies; BUSINESS & ECONOMICS -- Real Estate -- General; Water resources development -- International cooperation; Water-supply -- Economic aspects; Water-supply -- Management -- International cooperation; Watershed management -- International cooperation; Electronic books; Case studies; Electronic books; Case studies